On coercive solvability of operator-differential equations in $B$-spaces - Dzhabrailov, M. S. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the coercive solvability of operator-differential equations in anisotropic B-spaces of vector-functions.